A criterion for the existence of soliton solutions of telegraph equation - Kal’menov, T.Sh.; Arepova, G.D. (Bulletin of the Karaganda University. Mathematics Series, 2018)
In this paper we consider a telegraph equation. In the case of a rectangular domain for the Cauchy potential the lateral boundary conditions obtained. When considering the equation in the first quadrant a criterion for the existence of soliton solutions is obtained.